Polystyrene-diazonium-salt-based hydrophilic modification method for polyurethane - QIU SONG; YANG FANGFANG; WEI LINGYONG; LI XINYANG (2018)
The invention relates to a polystyrene-diazonium-salt-based hydrophilic modification method for polyurethane. The polystyrene-diazonium-salt-based hydrophilic modification method comprises: 1, metering an appropriate amount of a polystyrene diazonium salt solution, and soaking a polyurethane carrier in the polystyrene diazonium salt solution for a certain time at a certain temperature; and 2, taking out the polyurethane carrier after completing the soaking, washing with water, blowing for a certain time with cold air, soaking the polyurethane carrier in an anionic polyelectrolyte solution, carrying out adsorption soaking for a certain time at a certain temperature, taking out, and carrying out blow drying so as to complete the hydrophilic modification process of the polyurethane carrier. According to the present invention, the anionic polyelectrolyte is immobilized on the surface of the polyurethane by using the multifunctional group property and the high reactivity of the polystyrenediazonium salt so as to a